Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Answer:
x = √17 and x = -√17
Step-by-step explanation:
We have the equation:
[tex]\frac{3}{x + 4} - \frac{1}{x + 3} = \frac{x + 9}{(x^2 + 7x + 12)}[/tex]
To solve this we need to remove the denominators.
Then we can first multiply both sides by (x + 4) to get:
[tex]\frac{3*(x + 4)}{x + 4} - \frac{(x + 4)}{x + 3} = \frac{(x + 9)*(x + 4)}{(x^2 + 7x + 12)}[/tex]
[tex]3 - \frac{(x + 4)}{x + 3} = \frac{(x + 9)*(x + 4)}{(x^2 + 7x + 12)}[/tex]
Now we can multiply both sides by (x + 3)
[tex]3*(x + 3) - \frac{(x + 4)*(x+3)}{x + 3} = \frac{(x + 9)*(x + 4)*(x+3)}{(x^2 + 7x + 12)}[/tex]
[tex]3*(x + 3) - (x + 4) = \frac{(x + 9)*(x + 4)*(x+3)}{(x^2 + 7x + 12)}[/tex]
[tex](2*x + 5) = \frac{(x + 9)*(x + 4)*(x+3)}{(x^2 + 7x + 12)}[/tex]
Now we can multiply both sides by (x^2 + 7*x + 12)
[tex](2*x + 5)*(x^2 + 7x + 12) = \frac{(x + 9)*(x + 4)*(x+3)}{(x^2 + 7x + 12)}*(x^2 + 7x + 12)[/tex]
[tex](2*x + 5)*(x^2 + 7x + 12) = (x + 9)*(x + 4)*(x+3)[/tex]
Now we need to solve this:
we will get
[tex]2*x^3 + 19*x^2 + 59*x + 60 = (x^2 + 13*x + 3)*(x + 3)[/tex]
[tex]2*x^3 + 19*x^2 + 59*x + 60 = x^3 + 16*x^2 + 42*x + 9[/tex]
Then we get:
[tex]2*x^3 + 19*x^2 + 59*x + 60 - ( x^3 + 16*x^2 + 42*x + 9) = 0[/tex]
[tex]x^3 + 3x^2 + 17*x + 51 = 0[/tex]
So now we only need to solve this.
We can see that the constant is 51.
Then one root will be a factor of 51.
The factors of -51 are:
-3 and -17
Let's try -3
p( -3) = (-3)^3 + 3*(-3)^2 + +17*(-3) + 51 = 0
Then x = -3 is one solution of the equation.
But if we look at the original equation, x = -3 will lead to a zero in one denominator, then this solution can be ignored.
This means that we can take a factor (x + 3) out, so we can rewrite our equation as:
[tex]x^3 + 3x^2 + 17*x + 51 = (x + 3)*(x^2 + 17) = 0[/tex]
The other two solutions are when the other term is equal to zero.
Then the other two solutions are given by:
x = ±√17
And neither of these have problems in the denominators, so we can conclude that the solutions are:
x = √17 and x = -√17
We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.